The Butcher's Tongue Illusion. (August 2014) - Michel, Charles; Velasco, Carlos; Salgado-Montejo, Alejandro; Spence, Charles
We report two experiments, based on a novel variant of the Rubber Hand Illusion (RHI), in which tactile stimulation is referred to an artificial (out-of-body) tongue. In the experiments reported here the participant's tongue was stimulated while they looked at a mirrored dummy tongue. On average, the participants agreed with the statement that they felt as if they had been touched in the location where they saw the rubber tongue being touched (experiment 1), thus demonstrating visual capture. When the external tongue was illuminated with a laser pointer (experiment 2), a significant proportion of the participants reported feeling either tactile or thermal stimulation on their own tongue. These results therefore demonstrate that the multisensory integration of visual, tactile, and proprioceptive information that gives rise to the RHI can be extended to the tongue (a body part that is rarely seen directly).